Biomechanical properties of off-axis screw in Pauwels III femoral neck fracture fixation: Bicortical screw construct is superior to unicortical screw construct. Issue 11 (November 2019) - Kuan, Fa-Chuan; Hsu, Kai-Lan; Lin, Cheng-Li; Hong, Chih-Kai; Yeh, Ming-Long; Su, Wei-Ren
Highlights: To optimize the treatment of Pauwels type III femoral neck fracture, the manuscript conducts a biomechanical study to compare the unicortical off-axis screw with the bicortical one. An off-axis screw should be placed in bicortical fashion, which exhibited significantly higher axial stiffness and failure load. The off-axis screw placed in a unicortical fashion had the lowest resistance to interfragmental displacement. Abstract: Objectives: The purpose of this study is to determine the biomechanical properties of the bicortical off-axis screw fixation for stabilizing of Pauwels III femoral neck fractures compared with other fixation methods. Methods: Eighteen synthetic femurs (Sawbones Pacific Research Laboratories, Vashon, WA) were divided into three groups. The osteotomy was made vertically to mimic the Pauwels type III femoral neck fracture. Group A (n = 6) was fixed with traditional inverted triangle cannulated screws. Group B (n = 6) was fixed with a unicortical off-axis screw and two parallel cannulated screws. Group C (n = 6) was fixed with a bicortical off-axis screw and two parallel cannulated screws. Each group was tested with a nondestructive axial compression test at a 7° of valgus followed with 1000 cycles of cyclic loading test from 100 N to 1000 N. Finally, a destructive axial compression test was applied until catastrophic failure. Results: The average axial stiffness from group A to group C was 856.5, 934, and 1340 N/mm, respectively. The average ultimate failure load from group A to group C was 2612.7, 2508.8, and 3706 N, respectively. Group C exhibited significantly greater axial stiffness and a higher ultimate failure load than the other two groups (P < 0.05). Regarding the interfragmental displacement, the values from group A to group C were 0.41, 0.83, 0.36, respectively, and group B exhibited significantly larger fracture gap formation after the cyclic loading test. Conclusions: The results of this biomechanical study show statistically significant increases in axial stiffness and ultimate failure load for the off-axis screw placed in bicortical fashion. Once the off-axis screw was positioned unicortically, the largest fracture diastasis was observed as compared to the other two methods.